The Impact of the covid-19 pandemic on the distribution process and the appropriate target of zakat funds in Baitul Mal, Aceh Tamiang regency - Yana Athiyah; Mutia Sumarni (Prodi Manajemen Zakat dan Wakaf, Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Langsa, 2023)
Abstract Purpose – This research was conducted to determine how the impact of the Covid-19 pandemic on the distribution process and appropriate target of zakat funds in Baitul Mal Aceh Tamiang. Method – In this study using a descriptive method with a qualitative approach with primary and secondary data. Data collection methods are used by observation, interviews, and documentation. The informants of this study were two people from Baitul Mal Aceh Tamiang and five respondents who had the status of mustahik in Baitul Mal Aceh Tamiang. Respondents were selected based on considerations. First, Baitul Mal leaders or employees. Second, mustahik who have received zakat are described as follows: Results – The results of this study show that the distribution and appropriate of the target of zakat funds during the Covid-19 pandemic has many changes. Starting from changes in program planning, organizing that has changed the pattern of registration flow, the implementation of distribution has also changed by visiting the mustahik location directly and transferring via bank account, as well as supervision carried out before and after zakat funds are distributed. Lastly, the appropriate target during the Covid-19 pandemic remains well distributed even though Baitul Mal has not implemented a muqayyad (bound) zakat fund system and target appropriate during the Covid-19 pandemic has a broad view of which mustahik is entitled to receive it due to loss of income and other difficulties. Practical Implications – As a practical implication, the results of this study can be used as a reference to improved comprehend how attitudes and regulations must be engaged to make all changes due to the pandemic.